2008
DOI: 10.1093/jnci/djn011
|View full text |Cite
|
Sign up to set email alerts
|

Improved Survival of Patients With Human Papillomavirus-Positive Head and Neck Squamous Cell Carcinoma in a Prospective Clinical Trial

Abstract: For patients with HNSCC of the oropharynx, tumor HPV status is strongly associated with therapeutic response and survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

123
2,150
16
50

Year Published

2009
2009
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 2,486 publications
(2,339 citation statements)
references
References 19 publications
123
2,150
16
50
Order By: Relevance
“…Seven years later, in 1983, we published the first evidence suggesting that a subgroup (some 20 %) of oral cancers is associated with HPV, based on detection of HPV structural proteins in these lesions using an antibody prepared against pooled HPV types [39]. We subsequently identified HPV types 11, 16 and 18 in these samples [40][41][42][43][44][45][46][47][48][49]. This concept has now been well accepted, and a growing body of evidence is supporting that approximately 20 % of oral cancers and 60-80 % of oropharyngeal cancers are caused by HPV [41][42][43][44].…”
Section: Hpv and Head And Neck Cancer (Hnscc)mentioning
confidence: 99%
See 2 more Smart Citations
“…Seven years later, in 1983, we published the first evidence suggesting that a subgroup (some 20 %) of oral cancers is associated with HPV, based on detection of HPV structural proteins in these lesions using an antibody prepared against pooled HPV types [39]. We subsequently identified HPV types 11, 16 and 18 in these samples [40][41][42][43][44][45][46][47][48][49]. This concept has now been well accepted, and a growing body of evidence is supporting that approximately 20 % of oral cancers and 60-80 % of oropharyngeal cancers are caused by HPV [41][42][43][44].…”
Section: Hpv and Head And Neck Cancer (Hnscc)mentioning
confidence: 99%
“…Importantly, HPV-positive HNSCCs differ remarkably from HPV-negative HNSCCs in their clinical response and molecular properties. HPV-positive HNSCCs have a better overall-survival than HPV-negative HNSCCs [46,47]. HPV-positive HNSCCs harbor the wild-type p53, while the classical smoking-and alcohol-induced cancers have mutated p53.…”
Section: Hpv and Head And Neck Cancer (Hnscc)mentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have confirmed that patients with HPVrelated oropharyngeal cancer have a better prognosis than patients with tumors not associated with HPV. 15,16 To date, this has not led to any change in the treatment or staging of these malignancies, and has not been applied to a systematic method of adjusting prognosis. 17 However, future clinical trials may attempt to decrease the intensity of treatment in this subset of patients to limit morbidity, thereby taking advantage of the less aggressive biology of HPV-related tumors.…”
Section: Oncologic Prognosismentioning
confidence: 99%
“…Patients with HPV-positive OSCC are on average 5 years younger than HPV-negative patients, have higher lifetime number of vaginal-sex and oral-sex partners, higher prevalence of oral HPV infection, and lower incidence of alcohol and tobacco use [8]. HPV status in OSCC is also a powerful prognostic indicator with HPV-positive OSCC patients having a 58 % reduction in the risk of death when compared to patients with HPV-negative OSCC [2,9]. Pathologically, most HPV-positive OSCCs exhibit non-keratinizing or basaloid morphology [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%